2019
DOI: 10.3390/educsci9040263
|View full text |Cite
|
Sign up to set email alerts
|

People with Learning Disabilities and Smartphones: Testing the Usability of a Touch-Screen Interface

Abstract: Mobile phone technology is becoming ubiquitous. However, a number of unique usability challenges are still unresolved, including small screen size, device orientation changes, and an array of interaction methods (tap, flick, pinch, etc.) These challenges may be particularly acute for people with learning disabilities. This study examined the usability of touchscreen interactions, the difficulties, and possible solutions. An app was developed in which (12) participants accessed Google Maps and manipulated it to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Sadly, the necessary technology has often been inaccessible for those unable to write and read (Chadwick, Wesson, & Fullwood, 2013;Hegarty & Aspinall, 2006;Williams & Shekhar, 2019). An example can be any technology dependent on a keyboard.…”
Section: Persons With Id Participating In a Digitalised Societymentioning
confidence: 99%
“…Sadly, the necessary technology has often been inaccessible for those unable to write and read (Chadwick, Wesson, & Fullwood, 2013;Hegarty & Aspinall, 2006;Williams & Shekhar, 2019). An example can be any technology dependent on a keyboard.…”
Section: Persons With Id Participating In a Digitalised Societymentioning
confidence: 99%
“…The checkpoints of simple gestures, which appeared in both guidelines, were observed to be partially violated in half of the applications. It was found that 'tapping' was mostly used to interact with the interface, which would not be an issue, since dragging and multi-touch gestures were identified as difficulties during the evaluation of a touch-screen interface for individuals who experience intellectual disabilities [34]. While the checkpoint of minimizing the amount of information on each page was partially violated by 60% of apps and predominantly violated by 20% of apps.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies associate less frequent mobile phone use by people with intellectual disability with unsuitable design features of the devices, which, among other things, include unfriendly user interface and insufficient instructions (de Urturi Breton et al, 2012). Williams and Shekhar (2019) state that they may sometimes experience difficulties understanding the meaning of the icons or instructions which appear onscreen, or in situations when they are expected to type a required text or memorise a password and enter it correctly when unlocking the phone. Additionally, families of young people with mild intellectual disability are often overprotective of them.…”
Section: Discussionmentioning
confidence: 99%